Simulation of coupled fluid flow,heat transfer and solidification in slab continuous casting molds based on heat flux from an inverse model - LI Tian-yi; WANG Xu-dong; KONG Ling-wei; YAO Man; TIAN Yong; WEI Zu-kang; FENG Wei; FENG Guo-hui; QIAN Zhi-you (工程科学学报, 2016)
A three-dimensional mathematical model is developed based on the Navier-Stokes momentum equation and the low Reynolds number turbulence k-ε equation. This model comprehensively considers energy conservation,molten steel solidification and the influence of the mushy zone on the flow process. Heat flux obtained through an inverse heat transfer model combined with measured temperature is set as the boundary condition to the coupling model,to investigate fluid flow,heat transfer and solidification in the continuous casting mold. It is found that liquid steel flow has important influence on the distributions of temperature and heat flux,and the solidification process is governed by a synthetic action of fluid flow and heat flux. The proposed model and the non-uniform characteristic of solidification can provide reference for further investigation on longitudinal cracks and other surface defects during continuous casting.